11th Aerospace Sciences Meeting 1973
DOI: 10.2514/6.1973-187
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nozzle inlet shape, lip thickness, and exit shape and size on subsonic jet noise

Abstract: Far field noise data were taken for convergent nozzles of various shapes and sizes at subsonic velocities exceeding 400 feet per second. For a circular nozzle, the nozzle inlet shape and lip thickness had no effect on the noise level, directivity, or spectra when compared at the same nozzle exit diameter and peak exhaust velocity. A sharp edged orifice was one exception to this statement. Coannular nozzles can produce additional high frequency noise. Blunt ended centerbodies, where there is significant base dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…1, taken from Ref. 3, it is clearly shown that for coaxial nozzles the velocity ratio, VR, across the core nozzle lip has a strong effect on flow separation lip noise. When the velocity ratio was below 0.5 the lip noise was less than the broadband jet noise.…”
Section: Nozzles With Splitter Platesmentioning
confidence: 99%
See 3 more Smart Citations
“…1, taken from Ref. 3, it is clearly shown that for coaxial nozzles the velocity ratio, VR, across the core nozzle lip has a strong effect on flow separation lip noise. When the velocity ratio was below 0.5 the lip noise was less than the broadband jet noise.…”
Section: Nozzles With Splitter Platesmentioning
confidence: 99%
“…The noise from the nozzles listed above, all of which have regions of flow separation, will be discussed herein in order to tie in the Ref. 3 results with the new data contained. It is hoped that these few examples will impress upon the reader the importance of using nozzle designs that have no flow separation in jet noise experiments.…”
Section: Noise From Flow Separation Offmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. 6, some of the single stream jet noise spectral data obtained from this facility were compared to scaled up data taken by Lush in an anechoic chamber(7); the agreement was within the day to day repeatability.…”
Section: Acoustic Instrumentation and Data Analysismentioning
confidence: 99%